IMPLEMENTASI BLENDED LEARNING UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR MAHASISWA - Suryani, Dessy Rizki (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2021)
The purpose of this research is to know the improvement of student learning independence through the implementation of blended learning. The subject in this study were students of the Department of Mathematics Education, Musamus University, who took the differential equations course as many as 32 students. This classroom action research uses a Kemmis & Mc Taggart class action research cycle which is carried out in 2 cycles. Data collection techniques used in the form of documentation, observation and interviews. The documentation used are list of grades task and midterm exams, to measure student learning independence used learning independence observation sheet, as well as to determine student responses to implementation of learning using the interview method. Based on the analysis of the data obtained, the implementation of blended learning is able to increase student independence as evidenced by the results obtained there is an increase in the number of students who have learning independence. Pre-cycle learning independence data showed that 21.35% of students had aspects of learning independence, after the implementation of blended learning, the results in cycle 1 increased to 49.38% of students, and increased again in cycle 2 to 78.75% of students. With the implementation of blended learning, it is also able to improve student achievement as indicated by student achievement data. In cycle 1, the number of students who graduated was 46.88%, and increased in the implementation of cycle 2 to 71.88%